2015
DOI: 10.1159/000442982
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Subchronic Finasteride Treatment and Withdrawal on Neuroactive Steroid Levels and Their Receptors in the Male Rat Brain

Abstract: The enzymatic conversion of progesterone and testosterone by the enzyme 5alpha-reductase exerts a crucial role in the control of nervous function. The effects of finasteride in the brain, an inhibitor of this enzyme used for the treatment of human benign prostatic hyperplasia and androgenic alopecia, have been poorly explored. Therefore, the effects of a subchronic treatment with finasteride at low doses (3 mg/kg/day) and the consequences of its withdrawal on neuroactive steroid levels in plasma, cerebrospinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 63 publications
7
40
0
Order By: Relevance
“…This result indicated that the administration of finasteride in early developmental stage had no delayed effect on dopaminergic system and exploratory and motor behaviors in late adolescence, because the half‐life period of finasteride is around 6 hours only according to the instruction, and finasteride administrated at early developmental stage had been metabolized before rats developed to adolescent stage. A recent study showed that administration of 3 mg/kg finasteride to young adult rats for 20 days failed to induce changes of dihydrotestosterone level in the cerebral spinal fluid and brain tissue . In the present study, the same dose of finasteride treatment also did not elicit significant change in dopaminergic system or open‐field behaviors in adolescent rats.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…This result indicated that the administration of finasteride in early developmental stage had no delayed effect on dopaminergic system and exploratory and motor behaviors in late adolescence, because the half‐life period of finasteride is around 6 hours only according to the instruction, and finasteride administrated at early developmental stage had been metabolized before rats developed to adolescent stage. A recent study showed that administration of 3 mg/kg finasteride to young adult rats for 20 days failed to induce changes of dihydrotestosterone level in the cerebral spinal fluid and brain tissue . In the present study, the same dose of finasteride treatment also did not elicit significant change in dopaminergic system or open‐field behaviors in adolescent rats.…”
Section: Discussionsupporting
confidence: 51%
“…38 In the present study, for adolescent rats, finasteride was initially delivered at postna- A recent study showed that administration of 3 mg/kg finasteride to young adult rats for 20 days failed to induce changes of dihydrotestosterone level in the cerebral spinal fluid and brain tissue. 39 In the present study, the same dose of finasteride treatment also did not elicit significant change in dopaminergic system or open-field behaviors in adolescent rats. Taken together, the present findings that finasteride treatment inhibited dopaminergic system only in adolescent rats rather than early developmental rats suggested that finasteride inhibited dopaminergic system by inhibiting the activity of androgen.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…where dietary supplementation with salmon oil contaminated with a mixture of POPs in conjunction with high-fat (HF) diet feeding promoted the development of obesity and T2D in a rodent model 25, 26 , led to the proposition of a broader metabolism disrupting chemical hypothesis where ECDs act as metabolic disruptors that increase the susceptibility to metabolic diseases 7, 10, 27, 28 . A recent publication reviewed the putative mechanisms of metabolic disruption 28 , highlighting the effects on adipogenesis and adipokine production 29, 30 , neuroendocrine control of feeding and metabolism 31, 32 , energy homeostasis and T2D trough alteration of insulin action, glucose disposal and beta cell survival and function 33 , as well as hepatic steatosis 34 , and hyperlipidemia 35 . Involved molecular mechanism encompass the alteration of hormonal and homeostatic systems related to sex hormones (e.g.…”
Section: Introductionmentioning
confidence: 99%